Successful Treatment of Generalized Eruptive Keratoacanthoma of Grzybowski with Acitretin - Hélène Mascitti; Adèle De Masson; Florence Brunet-Possenti; Jean-David Bouaziz; Pauline Laly; Nadim Mourad; Jean-Michel Garrigues; Sara Laurent-Roussel; Bénédicte Cavelier-Balloy; Isabelle Moulonguet; Cristina Leschi; Samia Mourah; et al. (Adis, Springer Healthcare, 2019)
Abstract Introduction Keratoacanthomas (KA) are common cutaneous skin tumors originating from the hair follicles. Unlike squamous cell carcinoma, KA can regress spontaneously and have a benign evolution. Solitary KA is the most common form but familial multiple KA (Ferguson-Smith type), genetically predisposed KA (such as in xeroderma pigmentosum, or Muir-Torre syndrome), or sporadic multiple eruptive KA (Grzybowski type) have been described. Generalized eruptive KA of Grzybowski (GEKA) is a rare condition (around 40 reported cases). The pathophysiology is still unclear. Human papillomavirus (HPV) has been detected in sporadic KA but the presence of HPV39 has never been reported, to our knowledge, in GEKA. Case Report GEKA in an 80-year-old woman was successfully treated with acitretin (0.5 mg/kg/day) combined with surgical removal of the largest lesions. Treatment was well tolerated and led to decreased pruritus and tumor regression within 6 months. The presence of HPV39 was detected in a lesion by polymerase chain reaction and Sanger sequencing. No genetic alteration was found, in particular in the genes usually altered in squamous cell carcinoma (including NOTCH1, NOTCH2, CDKN2A, TP53). Conclusion We report a case of GEKA associated with the presence of HPV39 and the successful use of acitretin combined with surgical removal of the larger lesions.